Relasi Kuasa Kiai Pesantren dan Pejabat Publik dalam Merumuskan Kebijakan Pendidikan Islam di Madura (Analisis Teori Kekuasaan Michel Foucault) - Rusydiyah, Evi; AR, Zaini Tamin (Jurnal Review Politik, 2020)
One interesting political phenomenon today is the figure of the Kiai, who has a strong influence, both in communication and policy formulation. This study aims to analyze the relationship between pesantren Kiai and public officials in formulating Islamic education policies from the perspective of Michel Foucault. The method used in this research is qualitative by using naturalistic interpretative. Data collection techniques using interviews, observation, and capture literature. The results of this study reveal the relationship between pesantren Kiai and public officials are; 1) Patriarch. This relationship is a form of leadership that is based on relationships and leadership that is led. In social structure, Kiai is categorized as an elite structure. The Kiai has a strong formal and informal authority; 2) Collegial. This relationship is a bond or relationship like a partner or colleague (colleague). A collegial relationship occurs where several places can influence each other with different strengths. Both forms of relations in the Foucault’s opinion occur because the Kiai has the power of science and public power that has political power. Relations between the occur in the formality of the Madurese community.